Significantly lower femoral neck growth in screw fixation of the asymptomatic contralateral hip in unilateral slipped capital femoral epiphysis. Issue 3 (May 2016) - Wölfle-Roos, Julia V.; Urlaub, Stefanie; Reichel, Heiko; Taurman, Rita
Abstract : There is an ongoing debate on which fixation technique should be preferred for the prophylactic fixation of the asymptomatic contralateral hip in slipped capital femoral epiphysis (SCFE). In the case of Kirschner-wire (K-wire) fixation, there is a possibility of secondary loss of fixation because of longitudinal growth of the physis, whereas in screw fixation, physeal growth of the femoral neck might be impaired. The aim of this matched-pair study was to compare the longitudinal growth of the femoral neck in screw fixation versus K-wire fixation of the asymptomatic contralateral hip in SCFE. All 18 patients (female : male=3 : 15), who had undergone screw fixation of the asymptomatic contralateral hip between 9/2001 and 9/2011, were matched according to age, bone age, sex, and time to follow-up to another 18 patients with K-wire fixation. The length of the femoral neck of the contralateral hip was measured in parallel to either screw or K-wire from the apex of the femoral head to the opposite cortical bone. The ratio of the femoral neck length measured directly after surgery and on follow-up was defined as femoral neck growth. There was no significant difference between groups with respect to age, modified Oxford Bone age score, and time to follow-up. We found a significant difference in femoral neck growth between patients with screw fixation (5.5±4.3%) compared with K-wire fixation (8.9±5.7%, P =0.048 matched Wilcoxon test). The difference in femoral neck growth of patients with K-wire or screw fixation of the contralateral asymptomatic hip in SCFE was small, but statistically significant. Thus, despite high rates of secondary loss of fixation, K-wire fixation should still be considered, especially in very young patients.